CURRENT ROLE OF AUTOLOGOUS AND ALLOGENEIC STEM CELL TRANSPLANTATION FOR RELAPSED AND REFRACTORY HODGKIN LYMPHOMA - Luca Castagna; Carmelo Carlo-Stella; Rita Mazza; Armando Santoro (Mediterranean Journal of Hematology and Infectious Diseases)
Classical Hodgkin lymphoma (cHL) is a relatively rare disease, with approximately 9,200 estimated new cases and 1,200 estimated deaths per year in the United States. First-line chemo-radiotherapy leads to cure rates approaching 80% in patients with advanced-stage disease. However, 25 to 30% of these patients are not cured with chemotherapy alone (i.e., the ABVD regimen) and show either primary refractoriness to chemotherapy, early disease relapse or late disease relapse. Second-line salvage high-dose chemotherapy (HDC) and autologous stem cell transplantation (SCT) have an established role in the management of refractory/relapsed cHL, leading to durable responses in approximately 50% of relapsed patients and a minority of refractory patients. However, due to the poor responses to second-line salvage chemotherapy and dismal long-term disease control of primary refractory and early relapsed patients, their treatment represents an unmet medical need. Allogeneic SCT represents, by far, the only strategy with a curative potential for these patients. Despite a general consensus that early relapsed and primary refractory patients represent a clinical challenge requiring effective treatments to achieve long-term disease control, there has been no consensus on the optimal therapy that should be offered to these patients. This review will briefly discuss the clinical results and the main issues regarding autologous SCT as well as the current role of allogeneic SCT.